Leptospirosis, an emerging zoonotic disease in Malaysia - Thayaparan, S; Robertson, Ian D; Fairuz, Amran; MT, Abdullah; Lela, Suut (College of Pathologists, Academy of Medicine Malaysia., 2013)
Leptospirosis is an endemic disease in Malaysia and recently has received increasing attention mainly due to several recent incidents that have resulted in human mortality which have alarmed health professionals in Malaysia. The increasing incidence of leptospirosis in forested regions is associated with the bacteria infecting small wild mammals other than rats. Infection in wildlife could result in the introduction of new serovars to humans and domesticated animals. More research on leptospirosis and the screening of wildlife and humans near wildlife habitats is required to have a better understanding of the involvement of wildlife in the disease.